Tunable electronic properties of graphene - fully hydrogenated boron nitride heterostructure: A van der Waals density functional study. (September 2017) - Zhang, W.X.; Dong, M.M.; Li, T.T.; Gong, J.L.; He, C.
Abstract: The structural and electronic properties of Gr/BN and Gr/H-BN-H heterostructures have been systematically investigated on density functional theory with van der Waals corrections. The results indicate that the band gap of Gr/H-BN-H is about 0.024 eV (without an electric field) and 0.412 eV (with a strong electric field). Moreover, the increase of band gap of Gr/BN and Gr/H-BN-H heterostructures does not lead an obvious drop in their carrier mobility. Meanwhile, Gr/H-BN-H heterostructure has a larger tunable range of band gap and carrier mobility than Gr/BN heterostructure. These electronic properties highlight graphene/BN potential applications in nanodevices with low energy consumption. Highlights: We perform DFT-D calculations to investigate the properties of Gr/BN and Gr/H-BN-H heterostructures with E-field. E g of Gr/H-BN-H is 0.024 eV (without an electric field) and 0.412 eV (with a strong electric field). Gr/H-BN-H heterostructure has a larger tunable range of band gap and carrier mobility than Gr/BN heterostructure.